The relationship between match tackle outcomes and muscular strength and power in professional rugby league - Redman, K. J.; Wade, L.; Whitley, R.; Connick, M. J.; Kelly, V. G.; Beckman, E. M. (The Journal of Strength and Conditioning Research, 2022)
Tackling is a fundamental skill in collision sports, such as rugby league. Match success is largely dependent on a player's ability to complete tackles and tolerate physical collisions. High levels of strength and power are key physical qualities necessary for effective tackling because players are required to generate large forces while pushing and pulling their opponents. The aim of this study was to examine the relationship between tackle outcomes and strength and power qualities in professional rugby league. Fourteen rugby league players participated in this study. Maximal strength was assessed through 1 repetition maximum on the back squat, bench press, and bench pull. Lower-body vertical and horizontal powers were evaluated using a countermovement jump and standing broad jump (SBJ), respectively. Upper-body power was assessed on a plyometric push-up (PPU). Postmatch analysis of 5 National Rugby League matches was conducted to examine tackling outcomes. A series of Spearman's rank-order correlations were used to assess the relationship among match tackle outcomes and strength and power variables. Significant associations were observed between play-the-ball speed and SBJ peak power (rs = -0.74, p = 0.003), postcontact metres and PPU peak power (rs = 0.77, p = 0.002), losing the play-the-ball contest in defence with SBJ distance (rs = 0.70, p = 0.006), and ineffective tackles with PPU concentric impulse (rs = 0.70, p = 0.007). These results suggest the development and maintenance of full-body power to enhance the likelihood of positive tackle outcomes during professional rugby league match-play.